The neuromuscular, endocrine and mood responses to a single versus double training session day in soccer players - Sparkes, W.; Turner, A. N.; Cook, C. J.; Weston, M.; Russell, M.; Johnston, M. J.; Kilduff, L. P. (Journal of Science and Medicine in Sport, 2020)
Objectives: This study profiled the 24 h neuromuscular, endocrine and mood responses to a single versus a double training day in soccer players. Design: Repeated measures. Methods: Twelve semi-professional soccer players performed small-sided-games (SSG`s; 4 vs 4 + goalkeepers; 6 × 7-min, 2-min inter-set recovery) with neuromuscular (peak-power output, PPO; jump height, JH), endocrine (salivary testosterone, cortisol), and mood measures collected before (pre) and after (0 h, +24 h). The following week, the same SSG protocol was performed with an additional lower body strength training session (back-squat, Romanian deadlift, barbell hip thrust; 4 × 4 repetitions, 4-min inter-set recovery; 85% 1 rep-max) added at 2 h after the SSG`s. Results: Between-trial comparisons revealed possible to likely small impairments in PPO (2.5 ± 2.2 W kg-1; 90% Confidence Limits: ±2.2 W kg-1), JH (-1.3; ±2.0 cm) and mood (4.6; ±6.1 AU) in response to the double versus single sessions at +24 h. Likely to very likely small favourable responses occurred following the single session for testosterone (-15.2; ±6.1 pg ml-1), cortisol (0.072; ±0.034 ug dl-1) and testosterone/cortisol ratio (-96.6; ±36.7 AU) at +24 h compared to the double session trial. Conclusions: These data highlight that performance of two training sessions within a day resulted in possible to very likely small impairments of neuromuscular performance, mood score and endocrine markers at +24 h relative to a single training session day. A strategy of alternating high intensity explosive training days containing multiple sessions with days emphasising submaximal technical/tactical activities may be beneficial for those responsible for the design and delivery of soccer training programs.